2021
DOI: 10.2516/ogst/2020091
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamically consistent Darcy–Brinkman–Forchheimer framework in matrix acidization

Abstract: Matrix acidization is an important technique used to enhance oil production at the tertiary recovery stage, but its numerical simulation has never been verified. From one of the earliest models, i.e., the two-scale model (Darcy framework), the Darcy–Brinkman–Forchheimer (DBF) framework is developed by adding the Brinkman term and Forchheimer term to the momentum conservation equation. However, in the momentum conservation equation of the DBF framework, porosity is placed outside of the time derivation term, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The acid injection velocity is increased from 1.04 × 10 −7 m/s to 1.04 × 10 −4 m/s, and an acid-efficiency curve can be drawn from the simulation results. From the results, it is concluded that the two acid-efficiency curves of works [ 42 , 45 ] match each other well. In addition, both works indicate that the optimal injection velocity is 1.04 × 10 −6 m/s.…”
Section: Matrix Acidization Simulatormentioning
confidence: 72%
See 4 more Smart Citations
“…The acid injection velocity is increased from 1.04 × 10 −7 m/s to 1.04 × 10 −4 m/s, and an acid-efficiency curve can be drawn from the simulation results. From the results, it is concluded that the two acid-efficiency curves of works [ 42 , 45 ] match each other well. In addition, both works indicate that the optimal injection velocity is 1.04 × 10 −6 m/s.…”
Section: Matrix Acidization Simulatormentioning
confidence: 72%
“…A linear system can be constructed from one or more PDEs. For example, after discretization, the concentration equation in the DBF model ([ 37 42 ]): which is a PDE, forms a linear system, by which the acid concentration can be achieved. However, another linear system in the DBF model, which is the velocity-pressure linear system, is constructed from two PDEs, the momentum conservation equation and the mass conservation equation.…”
Section: The Linear System Librarymentioning
confidence: 99%
See 3 more Smart Citations